The Effect Of Perceived Quality, Image And Motivation On Interest Students' Choice Of Islamic Primary School (A Case Study At Ma'arif Gandu Elementary School, Mlarak Ponorogo) - Muhammad Ilyas Sutiyawan; Dhika Amalia Kurniawan; Suyanto (Islamic Business and Management Journal, 2023)
Education is something that someone must have and get, but the best education is the target of every parent and child in realizing their dreams. Education is a learning process so that students continue to develop abilities and strengths to be able to have a useful level of knowledge. There are many criminal and immoral cases in adolescents such as pregnancy outside marriage, the use of narcotics, promiscuity in adolescents and others due to the lack of religious education given and instilled by an educator or school to their students. This study aims to determine and explain the influence of perceptions of quality, image and motivation in increasing Guardian interest in choosing Islamic elementary schools in madrasah Ibtidaiyah Ma'arif Gandu Mlarak Ponorogo. Interest can be interpreted as a form of desire with the behavior and actions given by consumers in this case is the guardian of the Madrasah Ibtidaiyah Ma’arif. With the existence of different perceptions in each person indicates that they have a good view of the object in this case is Madrasah ibtidaiyah Ma'arif. The population in the study was the Guardian of Madrasah Ibtidaiyah Ma'arif with a sample of 60 respondents. Withdrawal of the sample by means of probability sampling with a simple random sampling technique, data analysis using multiple linear regression. The results showed that Simultaneously: Perception of Quality, Image, Motivation had a positive effect on Guardian Interest Madrasah Ibtidaiyah Ma'arif Gandu Mlarak Ponorogo. And partially (X1) Perception of quality has a negative and insignificant effect on the interest of Guardian Ma'arif Gandu Mlarak Ponorogo Madrasah Ibtidaiyah, with the results obtained a significant value of 0,247 ≥ 0,05 and a calculated t value of 1.171 ≤ t table 2,000, (X2) Image has a positive and significant effect on the interest of Guardian Ma'arif Gandu Mlarak Ponorogo Madrasah Ibtidaiyah, with the results of the study obtained a significant value of 0,019 ≤ 0,05 and t count 2.420 ≥ t table 2,000 (X3) Motivation has a Positive and Significant influence on the interest of Guardian Madrasah Ibtidaiyah Ma'arif Gandu Mlarak Ponorogo, with the results of the study obtained a significant value of 0,005 ≤ 0,05  and the t value of 2.915 ≥ t table 2,000. Based on the results of the study, the researchers suggested that the relevant institutions further improve the perception of Guardian the of school quality, although sometimes the views of someone with others are different. As well as prioritizing the image and motivation of the institution towards the interest of the Guardian of the Madrasah Ibtidaiyah Ma’arif to be superior brand.